1999
DOI: 10.1046/j.1440-1746.1999.01854.x
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of T cell antigen receptor variable β genes during the clinical course of patients with chronic hepatitis B

Abstract: These findings suggest that the skewing of the TcR family with multiclone is the result of T-cell responses to viral antigens in peripheral blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
(41 reference statements)
0
2
1
Order By: Relevance
“…This is in contrast with previous studies, where TCR CDR3 size diversity was analyzed in a combined population of CD4+ and CD8+ T cells obtained from patients with CHB (18, 19). …”
Section: Discussioncontrasting
confidence: 58%
“…This is in contrast with previous studies, where TCR CDR3 size diversity was analyzed in a combined population of CD4+ and CD8+ T cells obtained from patients with CHB (18, 19). …”
Section: Discussioncontrasting
confidence: 58%
“…Sugyo et al [27] monitored the TCR β chains of 4 healthy controls from 4 to 8 weeks, revealing that there was no significant change in the ratio. Many studies have confirmed that, in patients with viral infection or cancer, the frequency of antigen-specific TCRs differs [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Several techniques have been applied to analyze human TCR usage such as analysis with monoclonal antibodies specific for TCR V regions [17,18] or analysis by the polymerase chain reaction (PCR) with a primer located in C gene and different V gene family-specific primers [19][20][21][22][23][24]. However, these methods do not correctly reflect TCR usage nor do they provide detailed information on J gene segments or CDR3 sequences.…”
Section: Introductionmentioning
confidence: 99%